Análise e seleção de metodologia para mapeamento do Índice de Sensibilidade Ambiental ao óleo em ambientes terrestres: aplicação em trecho da Rodovia Anhanguera (SP-330) - Basilio, Thamiris Cristina Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Environmental sensitivity index maps for oil spilling (SAO maps) are an essential element on the planning of mitigating actions on soil and water contaminations. Highways come up as important pilot-areas for sensitivity to oil spilling studies on terrestrial environments, since they are one of the most used modals to transport oil and its derived products. In this context, the objective of this study is the analysis of bibliographic references that exist, both nationally and internationally, about environmental sensitivity in terrestrial environments to oil and select a methodology to be applied, with some adaptations, in a pilot-area, located at a small section of the Anhanguera Highway (SP-330). In the study, photointerpretation and geoprocessing techniques (physiographic partition, digital elevation models, fractures and water streams extraction) are used, besides the intense bibliographic research. Based on the Environmental sensitivity index (ESI) from National Oceanic and Atmospheric Administration (NOAA), a system with fifteen classes was organised, through the junction of five variables, each one representing three classes. This index will be named Terrestrial Sensitivity Index (IST), observing the following variables: declivity, water table level, water streams density and relative permeability. The area as a whole is considered of medium to high sensitivity, and the characteristics taken into account for this interpretation are related exclusively to the physical environment, since this study focuses only in this area, disconsidering biological and socioeconomic characteristics. The methodology of environmental sensitivity mapping for oil spilling applied to highways presented a satisfactory adequacy, and it can be reapplied to any environment in which the oil spilling reaches only the ... (Complete abstract electronic access below)

As Cartas de Sensibilidade Ambiental para Derrames de Óleo (Cartas SAO) são um elemento essencial para o planejamento de ações mitigadoras de graves contaminações de solos e águas. Às rodovias se destacam como importantes áreas-piloto para os estudos de sensibilidade a derrames de óleo em ambientes terrestres, uma vez que elas são um dos modais mais utilizados nas últimas décadas, para o transporte de derivados de petróleo. Neste contexto, o presente estudo tem como objetivo analisar o restrito referencial bibliográfico existente, no âmbito nacional e internacional, sobre a sensibilidade ambiental ao óleo em ambientes terrestres e selecionar uma metodologia a ser aplicada, com devidas adaptações, em uma área-piloto, localizada em um trecho da Rodovia Anhanguera (SP-330), que apresenta 10km de extensão e 3 de diâmetro, no município de Araras. Utilizam-se, no estudo, técnicas de fotointerpretação e geoprocessamento (compartimentação fisiográfica, modelo digital do terreno, extração de drenagens e fraturas), além de pesquisas bibliográficas. Baseado no sistema de Índice de Sensibilidade Ambiental (ISA) da National Oceanic and Atmospheric Administration (NOAA), um sistema com quinze classes foi composto, através da junção de cinco variáveis, cada uma representando três classes. Esse índice será denominado Índice de Sensibilidade Terrestre (IST), observando as seguintes variáveis: declividade, textura, profundidade do nível d'água (NA), densidade de drenagem e permeabilidade relativa. A área, como um todo, é considerada de sensibilidade média a alta, e as características levadas em consideração para esta interpretação estão relacionadas apenas ao meio físico, visto que este trabalho não considera as características bióticas e socioeconômicas, que também compõe ... (Resumo completo, clicar acesso eletrônico)
Keywords: Geologia; Cartas de sensibilidade ambiental a derramamentos de óleo; Rodovias; Geoprocessamento; Araras (SP)